2016
DOI: 10.1080/1360080x.2016.1211950
|View full text |Cite
|
Sign up to set email alerts
|

Muslim students’ cultural and religious experiences in city, suburban and regional university campuses in NSW, Australia

Abstract: Although there is much research about the growing ethnic and religious diversity on university campuses across the world, relatively little is known about the religious and cultural experiences of Muslim students on university campuses in Australia. We draw upon an analysis of a survey that was completed by 323 Muslim students who were studying at universities in New South Wales, Australia. While we argue that these places are post-secular, we discover that city campus tend to be more secular than regional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…They recognised, however, that there were restrictions to this in wider society and after graduation, particularly in relation to their career prospects. These responses reflect Possamai et al's (2016) research in Australia which found universities to be tolerant post-secular spaces in which diversity is embraced. The fact that this tolerance was not felt to exist in wider society, particularly in public life, set potential limits on the young people's autonomy.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…They recognised, however, that there were restrictions to this in wider society and after graduation, particularly in relation to their career prospects. These responses reflect Possamai et al's (2016) research in Australia which found universities to be tolerant post-secular spaces in which diversity is embraced. The fact that this tolerance was not felt to exist in wider society, particularly in public life, set potential limits on the young people's autonomy.…”
Section: Discussionmentioning
confidence: 53%
“…HEIs may also be important spaces in religious identity formation for young Muslims. Possamai et al (2016) argue that universities are post-secular spaces in which public expression of religiosity is tolerated and in which there are largely positive attitudes towards diversity. In their large-scale survey research in Australia, they found that Muslim students were confident to practice their religion as university students.…”
Section: Higher Education As the Site Of Studymentioning
confidence: 99%
“…Soekarno or Bung Karno Gunawan (2016), that, "this nation must be built by prioritizing character building, because character building can make Indonesia a great, advanced, glorious and dignified nation. Although Bung Karno did not expressly state the need to re-actualize the spiritual character of entrepreneurship, it was understood that entrepreneurship was widely recognized as a determinant factor in accelerating economic development (Masyita et al, 2011;Fonneland, 2012;Chu, 2007;Neubert et al, 2017;Possamai et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These can often be compromised where hostility is generally felt on UK campuses (Stevenson, 2017). Our own reading across research into Muslim students' experiences across the UK and abroad (including Asmar et al, 2004;Asmar, 2005;Modood, 2006;Nasir & Al-Amin, 2006;Oikonomidoy, 2007;Seggie & Sanford, 2010;Hopkins, 2011; Muslim students' university experiences 1391 Possamai et al, 2016;National Union of Students, 2018) highlights a number of themes characterising 'the Muslim student experience', including: a high level of importance placed on Islam; little report of outright discrimination/harassment, but high feelings of alienation, exclusion and covert discrimination; inaccessible university cultures which lack diversity and are inflexible towards Islamic lifestyles; dissonance between academic and social experiences; and accommodations and sacrifices being made when negotiating between faith and education.…”
Section: Deconstructing Homogeneity In Student Voice and Experiencementioning
confidence: 99%